Electrochemical and Thermodynamic Behaviour of Bi(III) with Oxalic Acid and Malonic Acid at DME in Aqueous Media - Paliwal, M.K.; Gupta, O.D. (Asian Journal of Chemistry, 2010)
The reduction of Bi(III) with oxalic acid and malonic acid is investigated polarographically in aqueous medium. Bismuth(III) formed 1:1, 1:2 and 1:3 complexes species with oxalic acid and with malonic acid. The stability constants of Bi(III) with oxalic acid and malonic acid were evaluated by the method of DeFord and Hume. The reduction of the system in each case is quasireversible and diffusion controlled, involving three electrons. The thermodynamic parameters have been determined. The stability constants of these species at 300 K for Bi(III) with oxalic acid are log β1 = 2.19, log β2 = 3.90, log β3 = 6.38 and at 310 K are log β1 = 2.41, log β2 = 3.95, log β3 = 6.07 and thermodynamic parameters free energy (Kcal mol-1), enthalpy (Kcal mol-1) and entropy (cal mol-1 deg-1) are -2.87, -46.83 and -0.14 (MX1), -5.12, -43.10 and -0.12 (MX2), -8.37, -40.48 and -0.10 (MX3), respectively. The stability constants of these species at 300 K for Bi(III) with malonic acid are log β1 = 1.95, log β2 = 4.00, log β3 = 6.14 and at 310 K are log β1 = 1.78, log β2 = 3.95, log β3 = 6.27 and thermodynamic parameters free energy (Kcal mol-1), enthalpy (Kcal mol-1) and entropy (cal mol-1 deg-1) are -2.56, -38.84 and -0.12 (MX1), -5.25, -42.02 and -0.12 (MX2), -8.06, -43.45 and -0.11 (MX3), respectively. The mathematical Mihailov's method has also been applied for the comparison of stability constants values obtained by graphical method.